Heroic humility : what the science of humility can say to people raised on self-focus - Worthington, Everett L., Jr., 1946-; Allison, Scott T. (American Psychological Association, 2018)
"As we shall see, research on narcissism, Machiavellianism, and psychopathy (i.e., the dark triad) and fragile self-esteem suggest that a me-first life orientation does not spread content widely throughout one's social network. Perhaps it is time to look to some new direction. That might be recapturing the classic virtue of humility and then practicing it with heroism even to self-sacrifice. But humility is not easy to develop or practice in an individualistic culture. It requires courage and moments of extraordinary heroism superimposed over a life of heroic self-sacrifice for the good of others. To help others, leadership is necessary. We thus combine humility, heroism, and leadership in this book. We hope you will be enriched, enlightened, and encouraged in your study of humility as you read these pages."--Preface. (PsycINFO Database Record (c) 2018 APA, all rights reserved)